2022
DOI: 10.7150/thno.75966
|View full text |Cite
|
Sign up to set email alerts
|

Intravital molecular imaging reveals that ROS-caspase-3-GSDME-induced cell punching enhances humoral immunotherapy targeting intracellular tumor antigens

Abstract: Tumor antigens (TAs)-induced humoral immune responses or TAs-specific antibodies have great application prospects for tumor therapy. However, more than half of TAs are intracellular antigens (intra-Ags) that are hardly recognized by antibodies. It is worthy to develop immunotherapeutic strategies for targeting intra-Ags. Methods: We used the far-red fluorescent protein tfRFP as an intracellular antigen to immunize mice and generated a liver metastasis model by injecting tfRFP-expressing B16 melanoma cells (tfR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…29c ), suggesting that all cells in a clone originating from a single tumor cell are identical in color. Then, we monitored the growth dynamics of tumor clones in a liver metastasis mouse model 48 , 49 created by intrasplenic injection of UFObow-B16 cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…29c ), suggesting that all cells in a clone originating from a single tumor cell are identical in color. Then, we monitored the growth dynamics of tumor clones in a liver metastasis mouse model 48 , 49 created by intrasplenic injection of UFObow-B16 cells.…”
Section: Resultsmentioning
confidence: 99%
“…The process of tumor cell colonization and colony formation in vivo was monitored through a liver window 48 , 50 for 9 days under an inverted confocal microscope equipped with a 405-nm laser (days 3, 5, 7, and 9) (Fig. 5a ).…”
Section: Resultsmentioning
confidence: 99%
“…This upregulation of ROS induced the activation of intracellular caspase‐3 (Figure 7), resulting in cell membrane perforation and the release of intracellular antigen tfRFP, which combined with an extracellular antibody to form an antigen–antibody complex. Further activation of the complement system accelerated and amplified the cell membrane perforation effect, while recruiting neutrophils and F4/80 + macrophages to the liver for synergistic antitumor effects [71].…”
Section: Intravital Optical Imaging Of Liver Immune Cellsmentioning
confidence: 99%
“…In the process of tumor development, genetically programmed changes occur in tumor cells and surrounding cells [70] (tfRFP)-labeled B16 cells expressing apoptosis-related probes, including reactive oxygen species (ROS), caspase-3, and calcium probes. Employing this model, they observed the immune response in liver metastasis using intravital optical molecular imaging [71]. They found that, at the early stage, B16 tumor cells injected into hepatic sinuses via the spleen were influenced by blood flow shear forces and metabolic changes and that the ROS level was gradually increased.…”
Section: Liver Tumorsmentioning
confidence: 99%
See 1 more Smart Citation